Synthèse d’entretien avec Monsieur Samandoulgou Basga - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This summary of an interview with anspecialist education associate, supervised education option, took place in Manga on April 30, 2021. During this interview, the participants discussed the typology of misconduct, as well as its management for both modern justice actors and traditional judicial bodies. The discussion also looked at the perception of punishment as a function of gender and social class, the meaning of mediation, and collaboration between traditional and modern institutions in the management of misconduct.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Maintenance; Prisons